The journey of ultrasound-based thyroid nodule risk stratification scoring systems: Do all roads lead to Thyroid Imaging, Reporting and Data System (TIRADS)? - Abhishek Mahajan; Tanvi Vaidya; Richa Vaish; Nilesh Sable (Journal of Head & Neck Physicians and Surgeons, 2017)
A number of qualitative and quantitative ultrasound (US) risk stratification systems for thyroid nodules are being used all over the world, new ones are being devised but so far, no consensus on a single system has emerged. Efforts by the worldwide medical community involved in the management of thyroid nodules are converging toward US risk stratification systems, which could provide a high-sensitivity and high-negative predictive value (NPV) for the diagnosis of clinically significant thyroid carcinomas. In this article, we review the fascinating journey of thyroid US-based thyroid imaging reporting and data system (TIRADS), the changing trends in TIRADS and emerging stratification systems to assess the risk of malignancy. Our recommendation is to develop a comprehensive system of risk stratification which incorporates clinically relevant as well as radiological risk factors and aims to accurately predict the risk of malignancy and oncologic outcome for each patient.